Climate change impacts and public perceptions - Petraki, Marianna (2016)
The impacts of climate change in the environment are beginning to be apparent, not just affecting the natural environment but also human societies. In Crete, according to the IPCC projections, these effects are highly likely to intensify in the coming decades. The temperature will rise, the frequency of rainfall will decrease, and the sea level rise will affect numerous coastal areas. Extreme weather events now make their appearance more and more frequently, causing disasters such as floods and droughts. These changes represent a serious threat to human life, economic development and the natural world, from which humans are depending largely their prosperity. Moreover, these changes affect in different levels and in different ways every society. In this thesis a general background will be provided regarding the climatic conditions and climate change future projections concerning the area of interest. The focal point of this work is to assess how the locals perceive, experience and understand climate change in the Heraklion regional unit. An attempt will be also made to analyze for the region the reasons that make basic domains of the society vulnerable to extreme weather events. The purpose of this is to understand to some level the reasons that increase the vulnerability of the local population when exposed to various stimuli, since the success of adaptation or mitigation strategies is subject to population dynamics along with other factors.